Budaya Puja Arahat Sivali di Wihara Siripada dan Wihara Vipassana Graha - Sugianto Sugianto (Jurnal Pelita Dharma, 2018)
This study aims to describe the form of culture in worship or respect for Venerable Sivali at Siripada Temple and Vipassana Graha Temple.This research is a qualitative descriptive study. The object of research is Sivali's puja culture. The subjects of the study were Buddhists who worshiped Arahant Sivali. The research was conducted in Tangerang and Lembang. The time of research began in January to June 2018. Techniques and instructors collect data using observation, interviews, and documentation. To test the validity of the research instrument carried out with a test of credibility, dependability, confirmation, and transferability of the results of the study. Data analysis using the Miles Huberman model.Based on the results of research and refinement, it can be concluded that: (1) The shape of the Arahant Sivali altar in the Siripada monastery is a temple building made of stone and inside is a statue of Sivali who is sitting cross-legged and holding a bowl; the Arahant Sivali altar at the Vipassana Graha monastery in the form of a roofed building, four pillars and without walls with the position of the Arahant statue Sivali standing with a cane, umbrella, curled in a bag. (2) Pujas activities are carried out by the people by being respectful, such as going out, having a proverb, offering amja puja, remembering good services and attaining Arahanthood; and pray by reading paritta and make a wish. (3) There are still people who have no understanding of Sivali; the purpose of respect is varied, namely imitating Arahant Sivali, increasing confidence, respecting, expecting blessings. The positive influence of the habit of respect is belief in being strong, happy and prosperous. Penelitian ini bertujuan untuk mendeskripsikan bentuk kebudayaan dalam pemujaan atau penghormatan terhadap Yang Mulia Sivali di Wihara Siripada dan Wihara Vipassana Graha. Penelitian ini merupakan penelitian deskriptif kualitatif. Objek penelitian adalah budaya puja Sivali. Subjek penelitian adalah umat Buddha yang memuja Arahat Sivali. Penelitian dilaksanakan di Tangerang dan Lembang. Waktu penelitian dimulai pada bulan Januari sampai dengan Juni 2018. Teknik dan instruman pengumpulan data dengan menggunakan observasi, wawancara, dan dokumentasi. Untuk menguji keabsahan data penelitian dilakukan dengan uji kredibilitas, dependabilitas, konfirmabilitas, dan transferabilitas. Analisis data menggunakan model Miles Huberman. Berdasarkan hasil penelitian dan pembahasan maka dapat disimpulkan bahwa: (1) bentuk altar Arahat Sivali di Wihara Siripada berupa bangunan candi yang terbuat dari batu dan di dalamnya terdapat rupang Sivali yang sedang duduk bersila dan memegang mangkuk; altar Arahat Sivali di Wihara Vipassana Graha berupa bangunan yang beratap, bertiang empat dan tanpa dinding dengan posisi rupang Arahat Sivali berdiri sambil membawa tongkat, payung, mangkuk yang tersimpan dalam tas;(2)     aktivitas puja dilakukan umat dengan cara bersikap hormat seperti ber-anjali, ber-namaskara, mempersembahkan amisa puja, mengingat jasa kebaikan dan pencapaian Arahat; dan berdoa dengan baca paritta dan harapan untuk diri sendiri dan keluarga;(3)    masih ada umat yang belum memiliki pemahaman terhadap Sivali; tujuan penghormatan bermacam-macam yakni meneladani Arahat Sivali, menambah keyakinan, sekadar menghormat, mengharapkan berkah. Tata cara penghormatan kepada Yang Mulia Sivali sama seperti penghormatan kepada objek yang pantas dihormati. Pengaruh positif kebiasaan menghormat adalah keyakinan menjadi kuat, hidup bahagia, dan sejahtera.